Diversity of saproxylic dance flies and long-legged flies (Diptera: Empidoidea) in a temperate deciduous forest in Quebec, Canada - Cumming, Jeffrey M.; Sinclair, Bradley J.; Brooks, Scott E.; Mlynarek, Julia; Wheeler, Terry A. (Zootaxa, 2018)
A large diversity of saproxylic Empidoidea from a temperate deciduous forest in southern Quebec is documented. Adults of 43 empidoid species representing 19 genera in 12 subfamilies and three families were collected from in situ sealed emergence traps placed over decayed logs of American beech (Fagus grandifolia Ehrhart) and sugar maple (Acer saccharum Marshall). The results of this technique give a clear indication of the saproxylic larval and pupal habitat of these species. The importance of Empidoidea as larval predators in decayed wood niches is noted.